2021
DOI: 10.15212/cvia.2021.0017
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Implementation of Primary PCI in the Management of STEMI in Egypt

Abstract: Introduction: Evidence-based guidelines recommend primary percutaneous coronary intervention (PPCI) be the mainstay reperfusion strategy for the treatment of ST-segment elevation myocardial infarction (STEMI) if it is performedin the proper time window. However, the Egyptian health care system is still struggling to provide such an important service. The aim of the present study, through a quantitative questionnaire, is to explore the current practice of STEMI management in Egypt, and to identify the barriers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Zeymer et al [7] reported that average time from symptoms onset to first medical contact was 221.6 ± 460.6 min which is significantly lower than in our study. Shaheen et al [9] studied the current practice of STEMI management in Egypt and reported that delay in seeking medical advice is the main cause of pre-hospital delay and 24% of patients presenting to PPCI hospitals arrive to the hospital within 2 h of chest pain which is significantly higher than in our study.…”
Section: Discussioncontrasting
confidence: 64%
“…Zeymer et al [7] reported that average time from symptoms onset to first medical contact was 221.6 ± 460.6 min which is significantly lower than in our study. Shaheen et al [9] studied the current practice of STEMI management in Egypt and reported that delay in seeking medical advice is the main cause of pre-hospital delay and 24% of patients presenting to PPCI hospitals arrive to the hospital within 2 h of chest pain which is significantly higher than in our study.…”
Section: Discussioncontrasting
confidence: 64%
“…Globally, acute myocardial infarction (AMI) is the leading cause of mortality ( Anderson & Morrow, 2017 ; Geng et al, 2022 ; Shaheen, Helal & Anan, 2021 ). Pulmonary infection is highly prevalent in patients with AMI undergoing percutaneous coronary intervention (PCI) and is associated with elevated mortality rates ( Piccaro de Oliveira et al, 2016 ; Putot et al, 2019 ; Truffa et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%